Perbandingan Hukum Ketenagakerjaan Indonesia dan Singapura Studi Kasus Pengupahan dan Perlindungan Pekerja - Robiatul Adawiyah; Sulis Suhartini; Enjum Jumhana (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
This study compares the labor laws of Indonesia and Singapore with a focus on wages and worker protection. This study uses comparative research methods to analyze the differences and similarities between the Employment Law No. 13 of 2003 in Indonesia and the Employment Act (Cap 91) in Singapore. The results of the study show that Singapore has higher wage standards and more comprehensive worker protection than Indonesia. This study recommends improving labor laws in Indonesia to improve workers' welfare and strengthen their protection.